(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This visual essay brings together images of work developed at Oficina dos Fios (FAV/UFG). Embroidery exercises are proposed throughout the academic semester, providing a space for experimentation and construction of shared learning. The project is guided by the poetics of solidarity, according to which aesthesis and poiesis are inseparable dimensions of the processes of feeling, thinking, doing, and concern the experience more than the object, the relationships established ’between’ and not the work of art itself as a product. In this sense, both the back of the embroidery and the right side have equal value. This interest recognizes the potential in the relationships between some possible discipline, more visible on the right side, and some creative disorder, on the back.